KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 9 PADANG - Ghazali, Akbar Maulana; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTÂ The purpose of the research is to describe the reading skills of students' news text comprehension, Second, to describe the skills of writing news texts of students, third, to describe the correlation of reading comprehension of news texts with news writing skills of students of class VIII at SMP Negeri 9 Padang. The population of this research is VIII grade students of SMP Negeri 9 Padang in the 2019/2020 school year, which is 245 students. The sample in this study was determined by proportional random sampling 25% of 49 students. The research data scores the results of reading text comprehension test scores and the scores of news text writing skills scores. The research instrument is an objective test for reading text comprehension skills and performance tests for news text writing skills. Research Results First, the reading skills of understanding the news text of good qualifying students (B). Second, the skills of writing news texts of good qualifying students (B). Third, there is a correlation between reading comprehension and news writing skills with news writing skills of VIII grade students of SMP Negeri 9 Padang with degrees of freedom n-1 at 95% confidence level. T value (5.55) is greater than t table (1.68), i.e. titung> ttabel (5.55> 1.68) thus H0 is rejected and H1 is accepted because the test results prove that tcount is greater than t table. It can be concluded that reading text comprehension skills are correlated with news text writing skills.Â Kata Kunci: Korelasi, Membaca Pemahaman, Teks BeritaÂ